Efforts to Increase Motivation to Learn Physics Through The Application of Problem Based Learning (PBL) - Ariani, Dian; Hasyim, Muthahharah; Ramayana, Andi (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This research is a Classroom Action Research which aims to increase the motivation to learn physics of grade XII students of SMAN 2 Selayar through a Problem Based Learning learning model on Direct Current Electricity material. The subjects of this study were 34 students of grade XII Mipa 1 SMAN 2 Selayar for the 2023/2024 academic year, consisting of 10 men and 24 women. The implementation of actions is carried out in two cycles, Cycle I as many as 4 meetings and Cycle II also 4 meetings. Data collection was carried out using observation and motivational questionnaires. The collected data is analyzed using quantitative and qualitative analysis. From the results of the analysis, it can be seen that the results of observations of student learning motivation in cycle I and cycle II increased at each cycle which can be seen on the average observation of student learning motivation increased from 68% in cycle I to 78% in cycle II, while the average results of student motivation questionnaires in cycle I of 79% increased to 85% in cycle II. Thus, the use of the Problem Based Learning learning model can Increase students motivation to learn physics. Keywords: Learning motivation, Physics, Problem Based Learning